Բեգլար Ամիրջանը՝ օպերային երգիչ - Գոռ Սալնազարյան (ՀՀ ԳԱԱ հրատ.)
Данная статья посвящена оперному творчеству первого армянского баритона, яркого представителя “Bell Canto” Беглара Амирджана (1868-1937). Репертуар Б. Амирджанa включал более 50 опер. Он выступал в Италии (1894- 1895), в крупных городах России (1895-1903, 1904-1916), в Тифлисе.This article is about first Armenian baritone Beglar Amirdjan (1868-1937), who was one of the finest artist of “Bell Canto”. In his repertoire he had more than 50 operas. He performed on the stages of Italy (1894-1895), in the large cities of Russia (1895-1903, 1904-1916) and in Tbilisi (1903-1904).
Keywords: Biography; Music